Sistem Pelayanan Customer Service dan Tiket Checkin PT KAI DAOP 8 Surabaya di Stasiun Gubeng - Nirawati, Lia; Aras, Aisyah Rachmayanti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Railway transportation is considered an efficient mode of transportation in Java Island because it can transport passengers and goods quickly and in large quantities. Regarded as a highly popular mode of transportation, PT KAI (Persero) is committed to providing the best service with the tagline